Amyloidosis-related echo features and mortality in patients with multiple myeloma. (3rd October 2022) - Cui, Z; Castagna, F; Hanif, W; Apple, S; Zhang, L; Tauras, J; Braunschweig, I; Kaur, G; Janakiram, M; Wang, Y; Fang, Y; Pellikka, P A; et al.
Abstract: Background/Introduction: Patients with multiple myeloma (MM) are at increased risk of developing AL amyloidosis. It was determined by screening fat pad and bone marrow biopsy that 38% MM patients had amyloidosis at time of diagnosis and the majority were asymptomatic (1). However, whether amyloidosis-related echo features in MM affect survival remains unknown (1, 2). Purpose: The goals of our study are to: 1) characterize prevalence of amyloidosis-related echo features in patients with multiple myeloma, 2) investigate whether decrease in longitudinal strain affect survival outcomes. Methods: Patients diagnosed with MM between Jan 1, 2000 and Dec 31, 2017 at our institution were identified through Clinical Looking Glass. Those with echo within 1 year after myeloma diagnosis and left ventricular ejection fraction (LVEF) greater than 40% were included. Global longitudinal strain (GLS) and LVEF measurements were done using EchoGo (Ultromics, Oxford, UK). The average of GLS obtained from apical 4-chamber and apical 2-chamber views was used for analysis, with decreased GLS defined as absolute value less than 18%. Statistical analysis was conducted with STATA13, using Chi square test and Kruskal-Wallis for univariable analysis and Cox regression model for survival analysis. Results: From a total cohort of 909 patients, 252 met inclusion criteria, of which 59 (23.4%) patients had decreased average GLS (see Table 1). Patients' mean age was 63±11 years, 44.8% were male and most were Black (42.7%) and the rest Hispanic (33.3%) and White (7.9%). Median follow up time was 4.25 years. The group with decreased GLS had lower percentage of females (22% vs 51.8%, p<0.01), higher percentage of previous MI (11.9% vs 1.6%, p<0.01) and more prior diagnosis of heart failure (20.3% vs 1.6%, p<0.01). Among patients with decreased GLS, five-year mortality rate was 63.3% compared to 46.0% in those with preserved GLS (p<0.036). Median survival time was 3.9 years among those with reduced GLS and 4.3 years in those without (see Figure 1; p<0.01). Reduced GLS correlated with decreased survival (HR 1.6, p=0.03) even after adjusting for demographic variables (age, gender, race), history of MI, history of CHF, Charlson comorbidity index, myeloma RISS stage, and LVEF (≥50% vs 40–50%). Forty-seven (18.6%) patients had end diastolic inter-ventricular septum (IVSd) thickness ≥1.2cm. Median GLS in patients with increased IVSd thickness was 19% compared to 21% in those without (p=0.01). Nine patients had the apical sparing strain pattern for amyloidosis. Total of 158 patients had bone marrow specimen stained with Congo-red with 7 (4.4%) testing positive. Median GLS was 19% in the group staining positive for Congo-red compared 21% in the group with negative stain (p=0.03). Conclusions: Decrease in GLS on baseline echo correlates with increased mortality in patients with MM and may be due to subclinical cardiac amyloidosis. Funding Acknowledgement: Type of funding sources: None.